2016
DOI: 10.1208/s12248-016-9888-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Functional Diarylurea Small Molecule Inhibitors of TRPV1 with Therapeutic Potential for Neuroinflammation

Abstract: Transient receptor potential vanilloid type 1 (TRPV1), a heat-sensitive calcium channel protein, contributes to inflammation as well as to acute and persistent pain. Since TRPV1 occupies a central position in pathways of neuronal inflammatory signaling, it represents a highly attractive potential therapeutic target for neuroinflammation. In the present work, we have in silico identified a series of diarylurea analogues for hTRPV1, of which 11 compounds showed activity in the nanomolar to micromolar range as va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…The docking program Surflex-Dock GeomX (SFXC) in SYBYL-X 1.3 was utilized to carry out the virtual screening and construction of PD-1-peptide complex in which the docking scores are expressed in −log 10 (K d ) [26]. The main protocols or parameters of docking are listed as follows [27,28,29,30,31]: (a) The “number of starting conformations per ligand” was set to 10, and the “number of max conformations per fragment” was set to 20; (b) the “maximum number of rotatable bonds per molecule” was set to 100; (c) flags were turned on for “pre-dock minimization”, “post-dock minimization”, “molecule fragmentation”, and “soft grid treatment”; (d) “activate spin alignment method with density of search” was set to 9.0; and (e) the “number of spins per alignment” was set to 12.…”
Section: Methodsmentioning
confidence: 99%
“…The docking program Surflex-Dock GeomX (SFXC) in SYBYL-X 1.3 was utilized to carry out the virtual screening and construction of PD-1-peptide complex in which the docking scores are expressed in −log 10 (K d ) [26]. The main protocols or parameters of docking are listed as follows [27,28,29,30,31]: (a) The “number of starting conformations per ligand” was set to 10, and the “number of max conformations per fragment” was set to 20; (b) the “maximum number of rotatable bonds per molecule” was set to 100; (c) flags were turned on for “pre-dock minimization”, “post-dock minimization”, “molecule fragmentation”, and “soft grid treatment”; (d) “activate spin alignment method with density of search” was set to 9.0; and (e) the “number of spins per alignment” was set to 12.…”
Section: Methodsmentioning
confidence: 99%
“…Building on their initial screen Feng et al [ 155 ] further investigated diaryl molecules and screened a library of diarylurea compounds. The rationale for the choice of this class of molecules is the observation, coming from the previous computational studies, of the crucial energetic role played by the interaction between the capsaicin amide group and the side chain of Thr550.…”
Section: Trpv1 As a Drug Targetmentioning
confidence: 99%
“…In other simulation studies, the conformational changes induced by PI(4,5)P 2 binding were investigated [71], and the binding sites of general anesthetics were identified [72]. In addition, Feng et al carried out MD simulations of human TRPV1 bound with agonist/antagonist to probe the ligand-binding-induced conformational changes and validate their homology model of human TRPV1 [73,74]. To elucidate the TRPV1 heat activation, one MD study simulated the transmembrane domain of TRPV1 at different temperatures, which observed transient partial opening of the channel [75].…”
mentioning
confidence: 99%